Afro-arab women and the media misrepresentation: a literary panacea (2017)
Over five decades, there has been a steady growth of interest in studying the representations of Afro-Arab women in media as shown by the increasing number of journal articles of scholars have who have abundantly discussed about the ugly images of these women that have been shown in western media for years. However, research lacks explanation and sufficing solutions to ameliorate such images. Therefore, this paper is an attempt to facilitate the understanding of Afro-Arab women images drawing on the bulk of the theorizing and explain how literature can help undo the mischiefs of misrepresentation. Moreover, it also explores the ways in which the teaching and the promotion of Arabic fiction can help dismantle the misrepresentation of Afro-Arab women in the Western media. Particularly, it demonstrates how Egyptian fiction writer Ikbal Baraka's Li-nazallasdiqa' ila-I-abad(Let's Remain Friends Foreverjcan be used to correct misrepresentations of Afro-Arab women that appeared in media for a long time.